Determination of the permeability of biological membranes to various chemical markers, including anti-HIV drugs - Pretorius, Erina (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Pathology. Medical Microbiology))--University of Stellenbosch, 2009.